ANALYSIS OF THE CAPACITY OF LiFePO 4 BATTERIES BASED ON THE RELEASED ELECTRONS - Krašovic, Matic; Virtič, Peter (Journal of Energy Technology, 2025)
The lithium iron phosphate battery, or LiFePO 4, has been analysed in this article. Initially, a comprehensive overview was provided concerning the properties and chemistry of batteries. Subsequently, the core focus of the research was addressed, which centred on quantifying the number of electrons released per 1 cm2 in 1 second in one cell in the battery during charging. Additionally, comparisons were made, to ascertain whether batteries with capacities lower than the one selected for this study impact the number of electrons released during charging, assuming constant battery voltage, cell surface area and current, or whether the number of released electrons remains unaffected by the capacity variations. The analysis was conducted analytically, and demonstrated transparently using the MATLAB software package.